Fabrication and calibration of a polymer inclusion membrane–based passive sampler for in situ fluoride monitoring in groundwater - Azzah, Anisah Nabilah; Rumhayati, Barlah; Fardiyah, Qonita; Fitratian, Rifnida Azmi Fitratian (Graduate School of Universitas Brawijaya, 2026)
Monitoring fluoride in groundwater is critical due to the adverse health effects associated with elevated concentrations, including dental and skeletal fluorosis. This study aims to develop and evaluate a passive sampling device based on a polymeric inclusion membrane (PIM) for in situ fluoride determination in groundwater systems. The PIM was composed of cellulose triacetate (CTA, 70%) as the base polymer, Aliquat 336-Cl (20%) as the carrier, and 1-decanol (10%) as the plasticizer, with 1 M NaCl employed as the receiving phase. Membrane characterization was conducted through structural, hydrophilic, and mechanical analyses to confirm its suitability for environmental applications. Calibration of the passive sampler was performed under controlled laboratory conditions by investigating transport kinetics and assessing the effect of varying fluoride concentrations in the feed phase. These experiments enabled the determination of sampling rate parameters and the establishment of calibration models prior to field deployment. The sampling rates (R?) obtained were 7.60 × 10?¹¹ m³ s?¹ from kinetic analysis and 5.56 × 10?¹¹ m³ s?¹ from calibration experiments, yielding an average R? of 6.58 × 10?¹¹ m³ s?¹. Then, the passive sampler was deployed to measure TWA fluoride concentrations in various groundwater samples. Variation in TWA and PIM-accumulated fluoride showed that the correlation isn’t always linear across all samples, indicating that environmental and matrix effects influence fluoride accumulation. This study highlights the potential of PIM-based passive samplers as a practical tool for groundwater monitoring, while emphasizing the importance of site-specific calibration to ensure accurate and reliable measurements.